Pendekatan Sulh dan Mediasi Sebagai Alternatif Terbaik Penyelesaian Sengketa Ekonomi Syariah - Abd . Rahman (ITB AAS INDONESIA Surakarta, 2021)
Abstract Abstrak ditulis dalam bahasa Inggris yang berisikan isu-isu pokok penelitian, tujuan penelitian, This article will discuss efforts to resolve sharia economic disputes using the Sulh (peace) and Mediation approach to achieve justice. The type of research used is library research with a normative juridical approach that connects phenomina with the rule of law. In conventional business as well as in disputes, conflicts or disputes sometimes occur and cannot be avoided. Settlement of disputes in court takes a long time, costs a lot and the result is win-lose, causing a feeling of being unfair to one of the parties. For this reason, the method of Sulh (peace) and Mediation in resolving sharia economic disputes is the choice of sharia economic actors. Peace and Mediation can be developed using various models such as: negotiation and arbitration. This dispute resolution model is more acceptable to the community, because philosophically the values of sulh (peace) and Mediation (seeking joint solutions) that exist in Islamic law already exist intrinsically in the culture of Indonesian society which is more based on deliberation and harmony in social life.